Combined Therapy of Open Heart Surgery and Cervical Sympathectomy - Berat Cihan, Hasan; . Erdal Ege, Dr; . Oner Gulcan, Dr; . Riza Turkoz, Dr; .Mustafa Pac, Dr (Annals of Medical Research, 2021)
None
Keywords: s : Raynaud disease, cervical sympathectomy, open heart surgery